Employee Representation and the Manager-to-Worker Pay Ratio - Lin, Chen; Schmid, Thomas; Sun, Yang (The Review of Corporate Finance Studies, 2026)
We study how involving employee board representatives in determining managerial compensation affects the within-firm pay ratio. The 2009 German Compensation Act shifted executive pay decisions to the entire supervisory board, amplifying employees’ influence at firms with parity employee representation. This reform resulted in increased manager-to-worker pay ratios, driven by higher managerial compensation, without corresponding changes in firm performance or manager turnover. The result is robust in matched samples and absent in falsification tests. Improved employee job security and weak wage increases point to a possible alliance between employees and managers, indicating shared governance may not necessarily reduce pay inequality.